Downregulation of MicroRNA-34c-5p facilitated neuroinflammation in drug-resistant epilepsy - Fu, Meng; Tao, Jie; Wang, Dongdong; Zhang, Zhiping; Wang, Xiaoli; Ji, Yonghua; Li, Zhiping (Brain research, 2020)
•MiR-34c-5p was down-regulated in drug-resistant epilepsy.•Down-regulation of miR-34c-5p led to increased expression of HMGB1 and IL-1β.•Aberrant expression of these molecules contributes to loss of hippocampal neurons.•MiR-34c-5p could be a potential therapeutic target for drug-resistant epilepsy. Drug-resistant epilepsy patients has aberrant inflammatory mediator levels. However, the mechanism of which is remains unillustrated. Here the molecular mechanism underlying the neuroinflammatory process in patients with drug-resistant epilepsy were investigated. Bioinformatics analysis revealed that miR-34c-5p was significantly downregulated in patients with drug-resistant epilepsy, compared to control population. Then, luciferase reporter assays indicated that HMGB1, inflammation-related mediators, was the target gene of miR-34c-5p. The kainic acid-induced epileptic rats were established and divided into drug-sensitive epilepsy and drug-resistant epilepsy according to their seizure behavior and EEG after antiepileptic drug administration. Downregulation of miR-34c-5p, elevated expression of HMGB1 and IL-1β had been found in rats with drug-resistant epilepsy, compared to drug-sensitive epilepsy rats. Aggravated hippocampal neuron loss was demonstrated in rats with drug-resistant epilepsy. The results from epileptic rats were subsequently validated from children with drug-resistant epilepsy. Analysis manifested that miR-34c-5p was obviously decreased, while HMGB1 was increased on serum of children with drug-resistant epilepsy. Our study highlights that decreased miR-34c-5p in drug-resistant epilepsy exacerbates neuroinflammation, which aggravates hippocampal neuron loss in epileptogenesis. Thus, miR-34c-5p could be considered as a potential noninvasive biomarker and shed novel light on the development of an effective therapeutic strategy for children with drug-resistant epilepsy in the future.